Ionospheric radio - Davies, Kenneth (Institution of Engineering and Technology, 1990)
This book is aimed at professional scientists, engineers and students who need an intermediate-level reference and/or text. Students of aeronomy and radio wave propagation are introduced to basic wave theory in absorbing, anisotropic and dispersive media and to the physics of production, loss, and movement of plasma in the ionosphere presence of the geomagnetic field.